Effectiveness of tacrolimus concomitant with biological disease-modifying antirheumatic drugs in patients with rheumatoid arthritis - Terabe, Kenya; Takahashi, Nobunori; Asai, Shuji; Hirano, Yuji; Kanayama, Yasuhide; Yabe, Yuichiro; Oguchi, Takeshi; Fujibayashi, Takayoshi; Ishikawa, Hisato; Hanabayashi, Masahiro; Hattori, Yosuke; Suzuki, Mochihito; et al. (Modern rheumatology, 2023)
ABSTRACT Objectives The study aimed to investigate the effectiveness and tolerance of biological disease-modifying antirheumatic drugs (bDMARDs) therapy administered concomitantly with tacrolimus (TAC) treatment in patients with rheumatoid arthritis. Methods 2792 patients who underwent therapy with five bDMARDs (etanercept: ETN, adalimumab, golimumab, tocilizumab, and abatacept: ABT) were enrolled. Among the study subjects, 1582 were concomitant methotrexate (MTX group), 147 were concomitant TAC (TAC group), and 1063 were non-concomitant MTX and TAC (non-MTX/TAC group). The primary outcome was the incident rate of discontinuation of bDMARDs by adverse events (AEs) or loss of efficacy. Results Concerning the analysis for each reasons of discontinuation, including AEs and loss of efficacy, the hazards ratio (HR) was significantly lower in the TAC group than in non-MTX/TAC groups (AEs: HR = 0.39, 95% confidence interval, 0.23–0.68, loss of efficacy: HR = 0.49, 95% confidence interval, 0.30–0.78). The loss of efficacy with the use of ETN and ABT was lower in the TAC group than in non-MTX/TAC groups. Concomitant TAC did not induce elevated risk for discontinuation of AEs in all bDMARD analyses. Conclusions Concomitant TAC with ABT or ETN showed higher retention rates than bDMARDs therapy without TAC or MTX. AEs did not increase over long-term observation.